Functional imbalance not functional evenness is the third component of community structure. (July 2022) - Ricotta, Carlo; Bacaro, Giovanni; Maccherini, Simona; Pavoine, Sandrine
Highlights: Functional richness, diversity and evenness are usually considered complementary facets of community structure. Here we show that functional evenness fails to properly capture the regularity of species abundances in functional space. We will thus introduce the notion of functional imbalance, an indicator of the strength of interaction between species abundances and their functional dissimilarities. Functional diversity always increases with increasing functional imbalance. Therefore, functional imbalance is a more appropriate indicator of this facet of community structure than functional evenness. Abstract: It is generally assumed that functional richness, diversity and evenness are complementary and, taken together, describe different facets of the distribution of species and their abundances in functional space. However, although these three primary components of community structure are commonly accepted by most community ecologists, measures of functional evenness usually fail to properly capture the regularity of species abundances in functional space. In this paper we will use an underexplored decomposition of Rao's index of functional diversity to introduce the notion of functional imbalance, an indicator of the strength of interaction between species abundances and their functional dissimilarities. Functional diversity always increases with increasing functional imbalance. Therefore, functional imbalance seems a more appropriate indicator of this facet of community structure than functional evenness. A worked example aimed at evaluating the influence of grazing on plant community structure showed that all proposed measures of functional imbalance were able to highlight the main functional changes of a dry calcareous grassland in Tuscany (Italy) following grazing exclusion.